2018
DOI: 10.1007/s10888-018-9397-7
|View full text |Cite
|
Sign up to set email alerts
|

The signaling effect of gasoline taxes and its distributional implications

Abstract: The Robert Schuman Centre for Advanced Studies (RSCAS), created in 1992 and directed by Professor Brigid Laffan, aims to develop inter-disciplinary and comparative research and to promote work on the major issues facing the process of integration and European society. The Centre is home to a large post-doctoral programme and hosts major research programmes and projects, and a range of working groups and ad hoc initiatives. The research agenda is organised around a set of core themes and is continuously evolvin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 69 publications
0
7
0
Order By: Relevance
“…A number of other studies have assessed the signalling effect of different types of excise taxes ( Brockwell, 2014 , , 2019 , Tiezzi and Verde, 2019 , Licari and Meier, 2000 ). For example, Licari and Meier focused on tobacco taxation and used longitudinal data on cigarette packs consumed per capita by U.S. state from 1955 to 1996.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of other studies have assessed the signalling effect of different types of excise taxes ( Brockwell, 2014 , , 2019 , Tiezzi and Verde, 2019 , Licari and Meier, 2000 ). For example, Licari and Meier focused on tobacco taxation and used longitudinal data on cigarette packs consumed per capita by U.S. state from 1955 to 1996.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, Tiezzi and Verde assessed gasoline taxation and found that a gasoline tax has an additional impact on demand, beyond the impact of the tax-inclusive price change ( Tiezzi and Verde, 2019 ). Consumers who were aware that price had changed because of a tax (and not due to other market fluctuations) were observed to reduce demand more than those who are unaware of the tax ( Tiezzi and Verde, 2019 ). The authors suggest this is consistent with the hypothesis that the tax signalled a more permanent price change, implying a higher sustained cost of gasoline consumption.…”
Section: Discussionmentioning
confidence: 99%
“…The longer jurisdictions delay carbon pricing, the greater is the exposure of firms to market and technological risks, reputational risks, policy and legal risks, and physical risks. 41 The four risks sets are discussed one by one below: First, in a low-carbon future, there will be reduced market demand for high-carbon products, increased demand for zero-and low-carbon products and services, and new, clean technologies may disrupt markets (TFCD, 2016 [84]). Carbon intensive assets thus loose value.…”
mentioning
confidence: 99%
“…The longer firms hold on to high-carbon assets, the more they take on market and technological risks (TFCD, 2016 [84]; OECD, 2018 [1]). Second, consumers that increasingly demand more sustainable products mean that firms who do not adapt to a net-zero future expose themselves to greater reputational risks (TFCD, 2016 [84]; OECD, 2018 [1]). Third, polluting firms may face litigation in the future due to the evolving product and producer responsibility requirements at international, national and state level.…”
mentioning
confidence: 99%
See 1 more Smart Citation